Resource-draining inbox: exploring how email incivility leads to job anxiety and depression - Rashid MS; Haar J (Emerald Publishing Limited, 2026)
Purpose – Email incivility is an emerging workplace issue. However, empirical evidence is limited, especially around indirect mechanisms and contextual factors that amplify or mitigate its detrimental effects. This article examines the influence of experienced email incivility on job anxiety and job depression through the mediation pathway of work rumination and also explores working-from-home (WFH) as a contextual moderating factor. Design/methodology/approach – This article is based on two samples from New Zealand. We collected data from 427 managers (Sample 1) and 654 employees (Sample 2). CFA was conducted using AMOS, and hypotheses were tested in SPSS using the PROCESS 4.0 program. Findings – Across both samples, we find that email incivility increases job anxiety and job depression directly and indirectly through work rumination (partial mediation). Results also show that WFH (hybrid work settings) is likely associated with heightened negative outcomes of email incivility for employees only, but not for managers. Practical implications – Organizations need to establish online communication norms and email etiquette rules. Synchronous communication (video conferencing) may be encouraged for important and time-sensitive tasks. Managers need to do regular check-ins and provide extra task and social support to WFH employees. Originality/value – This research enhances understanding of the indirect mechanisms that shape email incivility influence, especially around cognitive processes like rumination. It added to the workplace incivility literature by testing WFH as a novel contextual factor. Moreover, our work extended the incivility target profile beyond employees and provided evidence on managers.
Keywords: Email incivility; Work rumination; Job anxiety and job depression; Work from home; New Zealand